From Paris to Perth: Adopting an Annales perspective on the social history of the Internet in Western Australia - Pass, Glenn (University of Illinois at Chicago, 2004)
A new approach may be needed to interpret the history of a new technology, such as the Internet, within a local context. The Annales School, founded in France in 1929, brought a new approach to the study of history in the last century, introducing new methods and sources to the discipline. This paper will consider what this older, modernist perspective can contribute to a postmodern social history of the Internet in Western Australia. Despite apparent differences, it will be argued the integration of Annales style historiography, within a postmodern context, will provide a useful model to explore the history of a new technology, such as the Internet, within a local setting.